Differentiated working conditions, gender in the software industry of Jalisco, Mexico - Rodríguez, Laura (2021)
Globalization has intensified inequalities with the minimum of restrictions and responsibilities for big capital. The methodological analytical framework of Global Value Chains (CGV) is used. The leading Multinational Companies (MNCs) of the most important GVCs have turned their attention to countries that offer advantages to have lower production costs that are mainly achieved, offering jobs that maintain, reproduce and take advantage of the inequalities that capitalism has caused. Jalisco, Mexico is recognized in the sector, and two case studies of MNEs located there are analyzed, which presume favorable working conditions for their employees and although it was already found that men are predominantly hired, it is considered in some cases as a “ important area for the development of women's work. ”In this sense, it contributes to the theoretical postulates of feminist economics, that even when conditions exist in the industry, as well as policies and programs in companies aimed at eradicating DST and the SLG, the cultural factor plays an important role. In this sense, this contribution to the theory has implications for the generation of more effective public and business policies for this cause.